Legal Protections for Patients with Medical Conditions in Online Health Consultations - Ni Putu Devy Handayani; I Gusti Ngurah Parikesit Widiatedja; R.A. Tuty Kuswardhani (Dinasti Research, 2025)
Legal protections in telemedicine protect patients' rights, privacy, and care quality, but research often overlooks patients' perspectives. Therefore, understanding evolving legislation and patient-centered legal concepts improves patient care. This article aims to explore legal protections for patients with medical conditions in online health consultations. This study used a systematic literature review (SLR) approach to examine articles related to legal protections for patients, medical conditions, and online health consultations. We searched the Scopus and PubMed databases for articles in three categories: legal protections for patients, medical conditions, and online health consultations over the last five years (2019-2024). Using the Publish and Perish and Mendeley Reference Manager applications, we selected 389 papers from the Scopus database and 46 from the PubMed database based on specific criteria. Therefore, we conducted a PRISMA analysis on the 59 full-text research articles that we included. The results show that legal protections for patients in online health consultations include confidentiality, informed consent, licensure, data protection, emergency response protocols, professional standards, telemedicine compliance, care quality, and redress mechanisms. Solutions include streamlining licensing processes and enhancing cross-border regulations. The study emphasizes the need for patient advocacy, legal protection, data protection, and ethical compliance in online medical consultations, addressing barriers like dissatisfaction and lack of funds.